Pelatihan Pengolahan Kemiri dan Kacang Sacha Inchi Menjadi Produk Unggulan Lokal untuk Meningkatkan Perekonomian Masyarakat Desa Tanak Beak - Irman Muliadi; Satutik Rahayu; Novianti Ramdani; Lira Nurman Abista; Angga Mulyadin; Ni Putu Deanita Dewanti; Denda Naya Sagiantari; Ardian Kurnia Hanispi; Harfina Suharis Fiana; Reva Nur Ramadhani; Zulfia Salsabila (Indonesian Publication Center, 2026)
Tanak Beak Village possesses abundant potential in candlenut and Sacha Inchi bean commodities; however, their utilization remains suboptimal due to the community's dependence on selling raw materials at low market prices. This study aims to transform these local commodities into flagship products through processing training programs and digital marketing strategies to improve the community's economic welfare. The community service method was implemented through the University of Mataram's KKN PMD program over 45 days, encompassing preparation (surveys and interviews), implementation (product diversification and seminars), and evaluation stages. Research instruments included observation sheets, interviews, and pre- and post-test questionnaires. The results indicate that food technology intervention successfully processed candlenuts into